Forms of administrative and legal protection of the rights of children with disabilities - Pereverziev, Dmytro (Actual problems of law (Aktual’ni problemi pravoznavstva), 2020)
The article, based on the analysis of current legislation, international agreements and opinions of administrative scientists, examines the issues of forms of implementation of administrative and legal protection of the rights of children with disabilities. It is argued that the use of the institution of administrative and legal protection of rights, will ensure the manifestation of the rule of law and the formation of public consciousness in relation to such a category of members of society as children with disabilities. Emphasis is placed on the fact that disability is an evolving concept and that disability is the result of interactions between people with disabilities and relative and environmental barriers that hinder their full and effective participation in life of society on an equal footing with others. It is determined that the administrative and legal protection of the rights of children with disabilities is a means of influencing the public administration on the participants of public relations in order to remove existing barriers in society that prevent the proper realization of the rights and interests of such children. The author notes that the forms of administrative and legal protection of the rights of children with disabilities include a significant range of actions and measures taken by the public administration to protect the rights of children with disabilities to avoid discrimination on the grounds of disability and their smooth integration into society. It is determined that actions and measures taken by public administration bodies to protect the rights of children with disabilities are implemented in the form of legal, law enforcement, and law enforcement functions. It is argued that the forms of activity of public administration bodies in this area are a manifestation of their executive and administrative activities and the provision of appropriate administrative services to prevent violations in the field of rights, freedoms and interests of children with disabilities in the process of their socialization. persons who have violated the rights of such participants in public relations.